PENERAPAN MODEL PEMBELAJARAN MAKE A MATCH UNTUK MENINGKATKAN KEAKTIFAN BELAJAR PESERTA DIDIK KELAS V UPTD SD NEGERI 11 PAREPARE - Zaenal Susanto; Abdul Hakim; Naufal Qadri Syarif (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This study aims to describe how the Make A Match learning model is implemented, while also evaluating the increase in learning engagement among fifth-grade students at UPTD SD Negeri 11 Parepare regarding the "Cultural Diversity in Indonesia" topic. Utilizing a qualitative approach with a Classroom Action Research (CAR) design, this study was conducted in two cycles, each consisting of planning, implementation, observation, and reflection phases. The subjects of this research included one classroom teacher and 28 fifth-grade students. Data were collected through observation and documentation methods. The findings indicate that the implementation of the Make A Match model effectively improved the learning process and boosted student engagement. This is evident from the improvement in both teacher and student activities, which progressed from the "Fair" category in Cycle I to the "Good" category in Cycle II. Additionally, the percentage of student learning engagement mastery rose significantly, from 62.72% (moderate category) in Cycle I to 87.94% (high category) in Cycle II. In conclusion, the Make A Match learning model is proven effective in enhancing the learning engagement of fifth-grade students at the school.